Travertine occurrences along major strike-slip fault zones: structural, depositional and geochemical constraints from the Eastern Anatolian Fault System (EAFS), Turkey - Erol, Serap Colak; Ozkul, Mehmet; Aksoy, Ercan; Kele, Sandor; Ghaleb, Bassam (Taylor & Francis Ltd, 2015)
The Eastern Anatolian Fault System (EAFS) is a left-lateral strike-slip fault zone, 30km wide and 700km long, that is the second most important neotectonic structure of Turkey. In this study, relationship between travertine precipitation and tectonic activity of some segments along this major strike-slip fault zone has been investigated by a multidisciplinary research. Structural, sedimentological, geochemical and geochronological studies were conducted on several travertine occurrences along the Karlova-Bingol segment (KBS) and the Adyaman Fault Zone (AFZ) of the EAFS. The Balta travertine mass on the AFZ was cross-cut by many extensional fractures that were filled by calcite veins. Geochemical analyses of the calcite veins indicate that some are hydrothermal in origin, whereas others are non-hydrothermal. Hydrothermal circulation in the crust was caused intermittently by the left-lateral strike-slip movements that have oblique- to normal-slip components in both the (KBS) and the (BYS) segments. Our results suggest that, from at least 325ka until present, tectonic activity was consistently accompanied by travertine deposition. Based on dating of the travertine occurrences in the valley of the Goynuk Stream around Haclar and Elmal, it is concluded that the NE-trending KBS is currently still active.
17th Annual Meeting of Active Tectonic Study -- OCT 24-25, 2013 -- Akdeniz Univ, Antalya, TURKEY
Keywords: Eastern Anatolian Fault System; strike-slip faulting; travertine; vein calcite; U-Th dating